(untitled) (Konferensiyalar | Conferences, 2024)
As great significance of writing in both academic and professional setting, the skill assessment has already become one of the main research topics. In most cases, the evaluation of writing skills can be overlooked due to instructors lacking theoretical understanding or insufficient training. This issue is evident in assessing writing in English as a foreign language (EFL). Therefore, the importance of assessment literacy during the evaluation process is being emphasized by scholars. This paper aims to explore the basics of EFL writing assessment and to provide essential and relevant source for instructors to improve their writing skills and understanding. Moreover, the purpose of this paper is to assist in equipping teachers with essential knowledge about assessment in the field.